Chiral magnetic effect in protoneutron stars and magnetic field spectral evolution - Sigl, Günter; Leite, Natacha (Journal of cosmology and astroparticle physics, 2016)
We investigate the evolution of the chiral magnetic instability in a protoneutron star and compute the resulting magnetic power and helicity spectra. The instability may act during the early cooling phase of the hot protoneutron star after supernova core collapse, where it can contribute to the buildup of magnetic fields of strength up to the order of 10{sup 14} G. The maximal field strengths generated by this instability, however, depend considerably on the temperature of the protoneutron star, on density fluctuations and turbulence spectrum of the medium. At the end of the hot cooling phase the magnetic field tends to be concentrated around the submillimeter to cm scale, where it is subject to slow resistive damping.